Permasalahan Anak Asuh dan Aplikasi Pelayanan Konseling Terhadap Mereka - Yusida Imran (Indonesian Institute for Counseling, Education and Therapy (IICET), 2013)
The research is conducted by means of descriptive qualitative method. The subjects of this research all of the YAB orphans those are 25 children altogether. The research instruments are AUM-U 1,2 and 5, questionnaire as well as a documentation study. The data obtained are analyzed and described. The research findings show that (1) the problems that the orphans mainly face relate to their personal matters, career and jobs; (2) there are 9 types of counseling service that can be provided at YAB. However, those already provided service are information service and individual counseling service; (3) counseling services play significant roles in building the orphans’ self confidence, minimizing their psychological burden and solving their problems. Therefore, the writer recommends that the Foundation (YAB) utilize counseling services as one of the prioritized activities for handling orphans problems at YAB.